2005
DOI: 10.1016/s0012-3692(15)34468-8
|View full text |Cite
|
Sign up to set email alerts
|

Surprisingly High Prevalence of Anxiety and Depression in Chronic Breathing Disorders

Abstract: It is troubling that a mere 31% of COPD patients with depression or anxiety are being treated, particularly given their high prevalence in this population. Practical screening instruments may help increase the recognition of anxiety and depression in medical patients, as suggested by the excellent positive predictive value of the PRIME-MD in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
365
3
29

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(429 citation statements)
references
References 40 publications
21
365
3
29
Order By: Relevance
“…This is also consistent with the other investigators who have found that physical diseases (e.g., COPD) are related to psychiatric disorders. 15,30,31 Limitations and Strengths This study has several limitations. First, the measures used in this study were based on self-report and may include some respondent bias (e.g., individuals with negative affect might over-report depressive symptoms) or the under-reporting of cigarette smoking or doctor visits for a psychological problem.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is also consistent with the other investigators who have found that physical diseases (e.g., COPD) are related to psychiatric disorders. 15,30,31 Limitations and Strengths This study has several limitations. First, the measures used in this study were based on self-report and may include some respondent bias (e.g., individuals with negative affect might over-report depressive symptoms) or the under-reporting of cigarette smoking or doctor visits for a psychological problem.…”
Section: Discussionmentioning
confidence: 95%
“…15,56 Our findings are consistent with the findings of other investigators since psychological symptoms in emerging adulthood were related to physical diseases and symptoms later in adulthood, 56 which, in turn, were related to psychiatric disorders in adulthood. 30 One possible mechanism for this association is that psychological symptoms might increase the risk for both cigarette smoking and physical disease. 15 Our results demonstrated that physical disease/symptoms preceded family financial difficulty, which in turn was associated with psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Congestive Heart Failure (CHF), Chronic Obstructive Pulmonary Disease (COPD), Myocardial Infarction (MI)) [5][6][7][8][9][10][11][12]. Functional decline associated with chronic medical illness is often accompanied by depressive symptoms, which arise in 20% to 50% of chronically ill persons [13][14][15][16]. Depressive symptoms can reduce a patients' ability to cope with physical symptoms and adhere to medical treatment, causing increased health care utilization and cost [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Our study investigated the prevalence of both anxiety and depression disorders in male and female COPD and Bronchial Asthma patients with a wide range of disease severity. A recent study by Kunik et al 9 investigated the prevalence of anxiety and depression in a large sample of patients with chronic breathing disorders, including COPD, but the authors enrolled only patients who reported a significant level of anxiety and depression in a telephone screening. The significant findings of our study are as follows: (1) The prevalence of anxiety is very high as compared to depression in patients of both COPD and Bronchial Asthma; (2) Male patients have higher levels of anxiety and depression; (3) More patients had grade one dyspnoea followed by grade two and then grade one.…”
Section: Discussionmentioning
confidence: 99%